The case for extended thromboprophylaxis in medically hospitalised patients – not yet made. (16th March 2019) - Cao, Jacob Y; Lee, Seung Yeon; Dunkley, Scott; Adams, Mark; Keech, Anthony
Abstract: Background: The role of extended thromboprophylaxis is established for surgical patients, but not yet for hospitalised medical patients. Design: This systematic review and meta-analysis sought to explore the role of extended thromboprophylaxis for medically ill hospitalised patients. Methods: Medline, EMBASE and Cochrane Libraries were searched and five randomised controlled trials were identified, comprising 20, 046 extended and 20, 078 standard duration thromboprophylaxis patients. Results: Allocation to extended treatment, compared with standard duration therapy, significantly reduced the risk of symptomatic deep vein thrombosis (relative risk (RR) 0.47, 95% confidence interval (CI) 0.29–0.78, P = 0.003) and non-fatal pulmonary embolism (RR 0.59, 95% CI 0.39–0.91, P = 0.02). The risk of venous thromboembolism-related death was comparable between the extended and standard duration treatment groups (RR 0.81, 95% CI 0.6–1.09, P = 0.16). Extended treatment also doubled the risk of major bleeding (RR 2.04, 95% CI 1.42–2.91, P < 0.001), without significantly affecting the risk of intracranial bleeding or bleeding-associated death. The cost of preventing one symptomatic deep vein thrombosis and non-fatal pulmonary embolism was found to be £24, 972 (€27, 969) and £45, 148 (€50, 566), respectively, which outweigh the direct cost of managing established venous thromboembolism as previously reported. Conclusions: Extended duration thromboprophylaxis caused a reduction in the risk of venous thromboembolic events, but also a numerically comparable increase in major bleeding. Further trials are required in high-risk subpopulations who may derive mortality benefits from treatment. Only then could a change in current policy and practice be supported.